2012
DOI: 10.1371/journal.pone.0042022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chromosomal Inversions on the Yeast DAL Cluster

Abstract: Chromosomal rearrangements occur readily in nature and are a major reshaping force during genome evolution. Such large scale modifications are usually deleterious causing several fitness defects, but sometimes can confer an advantage and become adaptive. For example the DAL metabolic cluster in yeast was assembled in recent evolutionary times in the Hemiascomycetes lineage, through a set of rearrangements that brought together the genes involved in the allantoin degradation pathway. In eukaryotes, the existenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 48 publications
0
40
0
Order By: Relevance
“…Chromosomal rearrangements such as translocations and inversions are known to affect the mitotic and meiotic fitness of different yeast species (Avelar et al, ; Colson, Delneri, & Oliver, ; Naseeb et al, ; Naseeb & Delneri, ). It has been shown that S. cerevisiae strains carrying single gene inversions can cause fitness defects in nutrient‐limited media (Naseeb & Delneri, ). However, large chromosomal inversions in S. cerevisiae can be either lethal or neutral depending upon the environmental conditions (Naseeb et al, ).…”
Section: Cre‐loxp Mediated Recombinationmentioning
confidence: 99%
“…Chromosomal rearrangements such as translocations and inversions are known to affect the mitotic and meiotic fitness of different yeast species (Avelar et al, ; Colson, Delneri, & Oliver, ; Naseeb et al, ; Naseeb & Delneri, ). It has been shown that S. cerevisiae strains carrying single gene inversions can cause fitness defects in nutrient‐limited media (Naseeb & Delneri, ). However, large chromosomal inversions in S. cerevisiae can be either lethal or neutral depending upon the environmental conditions (Naseeb et al, ).…”
Section: Cre‐loxp Mediated Recombinationmentioning
confidence: 99%
“…cerevisiae and encodes the allantoin catabolism pathway. Allantoin is the degradation product of purines, but the enzymes for degrading purine ring systems is missing in yeasts (Cooper et al ., ; Naseeb and Delneri, ; Wong and Wolfe, ). Instead, allantoin is imported from the environment.…”
Section: Research Areasmentioning
confidence: 99%
“…The allantoin degradation pathway also includes genes for allantoin racemase ( DCG1 ) and an isoform of malate synthases ( DAL7 ). This cluster of six DAL genes is located in a 9.4 kb region near the right telomere of chromosome IX (Naseeb and Delneri, ; Wong and Wolfe, ). The DAL cluster present in N .…”
Section: Research Areasmentioning
confidence: 99%
See 2 more Smart Citations